Η Επίδραση της Τηλεφωνικής Παρακολούθησης από Νοσηλευτές στην Έκβαση Ασθενών με Καρδιακή Ανεπάρκεια - Protopapas, Andreas; Lambrinou, Ekaterini (My University, 2014)
Introduction: The reduction of re-hospitalization seems to be possible with the early detection of clinical deterioration in patients with heart failure by nurse specialists through telephone monitoring. Signs and symptoms of clinical deterioration can be identified 8-12 days prior to introducing people to the hospital. Aim: To investigate the effect of telephone intervention/monitoring in patients with heart failure by nurses on re-hospitalizations, quality of life and self-management of the disease. Method: The search for articles was the electronic databases Medline, Science Direct and Cochrane Library. In databases Medline and Cochrane Library, we used the combination of indexing words: "telephone", " telephone intervention", "telephone follow up", "heart failure", "nurse", while in the database Science Direct we used the advanced search option and keywords: "telephone", "heart failure", "nurse". Results: The literature search revealed 9 studies that met predefined inclusion and exclusion criteria. The analysis showed 4 studies with reduced re-hospitalization, 3 studies with improvement of the quality of life, and 2 studies with improved self-care behavior and self-management. Conclusions: Data collection and clinical status assessment via telecommunication is becoming popular as an intervention that helps to identify disorders that occur before hospitalization is needed. Further investigation and research is needed with comparable interventions and outcomes.
The effect of telephone intervention by nurses in patients with heart failure
Keywords: Heart failure; Nurse; Telephone; Telephone follow up; Telephone intervention